Exploring Playful Affordances: Integrating Small Urban Housing Spatial Elements for Toddler’s Play - Jingga, Azharine Purwa; Nuswantara, Kartika (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DRPM), ITS, 2026)
Urban housing often limits children’s play opportunities due to restricted space. This study explores how small urban homes can support toddlers’ play and development through affordance theory, using the Form-Affordance-Function (FAF) framework to link spatial form, perceived actions, and developmental outcomes. A qualitative case study of five households with children aged 2-5 years employed observations and caregiver interviews to identify perceptible and hidden affordances. Findings show that toddlers creatively engage with both designed and everyday spatial elements, such as floors, stairs, and furniture, transforming them into play opportunities that foster motor skills, independence, and imagination. Designed spaces provided clear, perceptible affordances, while alternative spaces revealed hidden ones through child-led adaptation. The study highlights children’s agency in constrained environments and offers insights for architects and caregivers to design flexible, developmentally supportive homes.